The synchronous improvement of thermal stability, mechanical properties, thermal conductivity of oxide dispersion strengthened Cu–Cr alloy by microalloying Si - Yaju Zhou; Shengming Yin; Qian Lei; Jianglei Fan; Shizhong Wei; Youwei Yan (Journal of Materials Research and Technology)
In this work, mechanical alloying combined with spark plasma sintering (SPS) processes were used to prepare Cu-0.65Cr-0.5Y-0.15Cu2O, Cu-0.65Cr-0.5Y-0.5Al-0.15Cu2O and Cu-0.65Cr-0.5Y-0.5Si-0.15Cu2O (wt%). The effects of the introduction of Al or Si on the microstructure, mechanical properties, thermal conductivity and thermal stability of ODS Cu alloy were studied. All three alloys exhibit heterogeneous mixed grain structures, including coarse and fine grains, with oxide nanoparticles uniformly distributed throughout the copper matrix. However, the addition of Al or Si leads to grain refinement and further refinement of the oxide nanoparticles. Compared with ODS Cu alloy, the ultimate tensile strength of ODS Cu–Cr–Si alloy increased from 554 MPa to 621 MPa, the elongation at break increased from 8.8% to 11%, and the thermal conductivity increased from 221.5 W m−1 K−1 to 262.3 W m−1 K−1, respectively. The ODS Cu–Cr–Si alloy also shows ultrahigh microstructural stability upon annealing at 600 °C for 50 h. The excellent strength, ductility and thermal conductivity comes mainly from the high-density coherent nano-Y2Si2O7 (<15 nm) dispersed in ultrafine grain Cu matrix. In addition, it is found that the microalloying Si and Al significantly improve the MA efficiency. These findings indicate that an ODS Cu alloy promising for application under high-temperature (HT) conditions can be produced effectively and efficiently by combining composition design and process optimization.